Immunoglobulin Fractions Isolated from Patients with Antiphospholipid Antibodies Prevent the Inactivation of Factor Va by Activated Protein C on Human Endothelial Cells - Borrell, Montserrat; Sala, Nuria; de Castellarnau, Conxita; Lopez, Silvia; Gari, Merce; Fontcuberta, Jordi (Thrombosis and Haemostasis, 1992)
We studied the effect of purified immunoglobulins (Ig) from 21 patients with antiphospholipid antibodies (aPL) on factor Va degradation by activated protein C (aPC) on cultured human umbilical vein endothelial cells (HUVEC). Sera from patients were tested on an ELISA aPL assay to determine the isotype with aPL activity. HUVEC were incubated with purified IgG or IgM fraction from controls or patients. Activated PC and factor Va were then added and factor Va degradation was measured after several reaction times. 13 of 14 IgM and 8 of 10 IgG from patients showed an inhibitory effect on factor Va degradation by aPC when compared with control Ig. We also observed the same inhibitory effect with patients’ Ig on studying the degradation of factor Va by aPC in a purified system containing aPC, protein S and phospholipids. These results suggest that aPL antibodies disturb the anticoagulant activity of aPC, which may contribute to the thrombotic tendency of these patients.